2013
DOI: 10.1097/prs.0b013e31829fe461
|View full text |Cite
|
Sign up to set email alerts
|

Complete Horizontal Skin Cell Resurfacing and Delayed Vertical Cell Infiltration into Porcine Reconstructive Tissue Matrix Compared to Bovine Collagen Matrix and Human Dermis

Abstract: Matrix texture and surface properties governed cellular performance on tissues. Although dense dermal compaction delayed vertical cellular ingrowth for Strattice, it allowed uncompromised horizontal resurfacing. Dense dermal compaction may slow matrix decomposition and result in prolonged biomechanical stability of the graft. Reconstructive surgeons should choose the adequate matrix substitute depending on biomechanical requirements at the recipient site. Strattice may be suitable as a dermal replacement at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…The decellularized dermis utilized here, Strattice, has been used successfully as an internally placed scaffold for treatment of subcostal hernia repair [ 54 ] and breast reconstruction [ 55 , 56 ]. Mirastschijski et al have found that the decellularized dermis may be best suited for dermal wound beds that require a higher mechanical load than in those previously mentioned [ 57 ]. While residual porosity does facilitate some AdMSC migration, the high mortality rate would make this an unsuitable scaffold for a cell seeded dermal wound treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The decellularized dermis utilized here, Strattice, has been used successfully as an internally placed scaffold for treatment of subcostal hernia repair [ 54 ] and breast reconstruction [ 55 , 56 ]. Mirastschijski et al have found that the decellularized dermis may be best suited for dermal wound beds that require a higher mechanical load than in those previously mentioned [ 57 ]. While residual porosity does facilitate some AdMSC migration, the high mortality rate would make this an unsuitable scaffold for a cell seeded dermal wound treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that epithelial resurfacing and vertical proliferation were reduced and delayed by application of dermal matrices without affecting apoptosis, cell differentiation, or basement membrane formation . Previous clinical reports have also shown the feasibility of simultaneously applying thin split‐thickness skin grafts over a collagen–elastin matrix for full‐thickness skin reconstruction in burns or cancer reconstruction but lacked an explanation on how the applied skin grafts received nutrients, in other words: how the “mechanism of take” of the skin graft occurred.…”
Section: Discussionmentioning
confidence: 99%
“…However, the subjective assessment of scar quality by use of the Vancouver Scar Scale was not validated for pigs, and an objective assessment of dermal thickness was lacking . We aimed at providing a scientific basis for the explanation of graft supply in a simultaneous application of a dermal matrix and split‐thickness skin graft …”
Section: Discussionmentioning
confidence: 99%
“…H-KC and hd-FB isolation and the cell culture experiments were described in our previous work [57]. In short, the procedure involves a peeling of the epidermis by dispase II (2 U/mL; Roche, Grenzach-Wyhlen, Germany) digestion and a digestion with 0.05% trypsin-ethylenediaminetetraacetic acid solution (T/E) (PAA; L11-003) for h-KC.…”
Section: Cell Isolation and Culturementioning
confidence: 99%